The Incidence of Post-infectious Irritable Bowel Syndrome, Anxiety, and Depression in Iranian Patients with Coronavirus Disease 2019 Pandemic: A Cross-Sectional Study - Farsi, Farnaz; Zonooz, Sanaz Rezaei; Ebrahimi, Zohreh; Jebraili, Hanieh; Morvaridi, Mehrnaz; Azimi, Tahereh; Sikaroudi, Masoumeh Khalighi; Heshmati, Javad; Khorrami, Soroush; Mokhtare, Marjan; Faghihi, Amirhossein; Masoodi, Mohsen (Turkish Journal of Gastroenterology, 2022)
Background: Irritable bowel syndrome refers to a subgroup of disorders of gut–brain interaction associated with stress-related symptoms, but gastrointestinal infection can also be considered the leading risk factor. It is well reported that coronavirus disease 2019 can also result in gastroenteritis. Therefore, this study aimed to evaluate the incidence of post-infectious irritable bowel syndrome and stressful status among coronavirus disease 2019 patients. Methods: This cross-sectional study was conducted on adults with coronavirus disease 2019 referred to the Infectious Disease Clinic in Iran from November 2020 to February 2021. Patients who met all eligibility criteria were included in the study. The data were collected using a demographic questionnaire, Rome IV criteria questionnaire, and Hospital Anxiety and Depression Scale. Results: Totally, the data obtained from 233 eligible patients (136 women, 97 men; mean age 38.41) 11.52 (years) were collected and analyzed, and 53.2% of the cases had a moderate coronavirus disease 2019. The analysis showed that 27 (11.6%) patients suffered from irritable bowel syndrome symptoms based on Rome IV criteria after the recovery from the infection. Also, Hospital Anxiety and Depression Scale-based symptoms of depression and anxiety that occurred with coronavirus disease 2019 were reported in 27.4% and 36.9%, respectively. Conclusion: Our finding illustrated that irritable bowel syndrome symptoms based on Rome IV could occur in post-infected coronavirus disease 2019 patients. Also, Hospital Anxiety and Depression Scale-based symptoms of depression and anxiety were more common in females and coronavirus disease 2019 infected patients with clinical symptoms including cough, shortness of breath, and sore throat. Cite this article as: Farsi F, Rezaei Zonooz S, Ebrahimi Z, et al. The incidence of post-infectious irritable bowel syndrome, anxiety, and depression in Iranian patients with coronavirus disease 2019 pandemic: A cross-sectional study. Turk J Gastroenterol. 2022;33(12):1033-1042.